2005
DOI: 10.1002/chin.200522211
|View full text |Cite
|
Sign up to set email alerts
|

Koboquinone A and B, New Metabolites of Kobophenol A in Rats.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…These in silico predicted interactions inhibit the binding of the SARS-CoV-2 spike protein with host ACE2, presumably by destabilizing the complex formation. Additionally, three metabolites (M1, M2, and M3) 26 , 27 of Kobophenol A were also found to bind at the ACE2/spike interface and ACE2 hydrophobic pocket with relatively high favorable docking energies in comparison to the other natural compounds in the library ( Table 1 ). The docking results suggest that Kobophenol A should be the top target for carrying out further in vitro studies targeting the ACE2/spike RBD binding domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These in silico predicted interactions inhibit the binding of the SARS-CoV-2 spike protein with host ACE2, presumably by destabilizing the complex formation. Additionally, three metabolites (M1, M2, and M3) 26 , 27 of Kobophenol A were also found to bind at the ACE2/spike interface and ACE2 hydrophobic pocket with relatively high favorable docking energies in comparison to the other natural compounds in the library ( Table 1 ). The docking results suggest that Kobophenol A should be the top target for carrying out further in vitro studies targeting the ACE2/spike RBD binding domains.…”
mentioning
confidence: 99%
“… 27 Kobophenol A metabolites [koboquinone A (M1), koboquinone B (M2), and koboquinone C (M3)] ( Scheme 1 ) were isolated from rats feces after oral administration. The three metabolites M1, M2, and M3 26 , 27 were considered as part of the in silico studies and were found to bind well with good docking energies of −9.73, −10.48, and −10.27 kcal/mol, respectively.…”
mentioning
confidence: 99%